The Effectiveness of Therapeutic Painting on Behavioral Problems among 10-12 Year Students - Bay-Mohammad Chenderi; Mohammad-Kazem Fakhri; Yarali Dousti (Shahid Beheshti University of Medical Sciences, 2021)
Background and Objective: Children with behavioral disorders may be exposed to various harmful effects on their health and well-being in the long run. The objective of this study was to determine the effect of therapeutic painting on behavioral problems among 10-12 years old children. Materials and Methods: The research method was quasi-experimental with pre-test and post-test. The statistical population of the study included 950 elementary school students in the city of Gonbad-e-Kavus in the academic year 2017-18 which were 950 children. In a multi-stage random sampling, 60 students were selected and categorized into two experimental and control groups. Martin's Art Therapy intervention was conducted for the experimental group, but no intervention was performed in the control group and the Rutter's Behavioral Questionnaire was used for data collection. Data were analyzed using one-way covariance analysis via SPSS software version 20. Results: The mean (SD) age was 10.4 (1.6) years old in the experimental group and the mean 10.6 (1.7) in the control group. The mean (SD) score of behavioral problems in the experimental group was 10.5 (7.9) in the pretest, which decreased to 5.7 (4.4) in the post-test (P<0.01). However, the mean (SD) score of behavioral problems was 10.6 (6.3) in the pretest and varied to 10.5 (6.8) in the post-test, which was not statistically significant. Conclusion: The study showed that therapeutic painting led to reduction of students' behavioral problems.